Danger, dirt and degenerates: The rebellious act of creativity - Alice Morris (Fields)
Creativity: a word often associated with fun, colour and play, a sentiment reflected in companies attempting to recreate it for profit. ‘Selfie museums’ (exhibition spaces in which social media influencers can take ‘selfies’ in aesthetically pleasing environments) like the Wondr Experience litter their spaces with similar childlike aesthetics, with the superficial goal of fostering creativity, but resulting in an endless stream of identical Instagram posts and more crucially, ticket sales. This paper reveals a darker and more authentic side to creativity, proposing that discomfort is an essential ingredient. The cute spaces for ‘plandids’ (planned candid photographs) and the beanbags and beer fridges of hipster design studios are juxtaposed by the revelation that to engage in creative thought you have to be in a state of apprehension. Graphic designers often follow the security of grids designed by the likes of Josef Müller-Brockman; however, the piece suggests that these methods lie within the realms of comfort. This tendency for playing it safe is possibly because of the consumerist society we live in – not many designers can afford to take risks because failure means no pay cheque. In such a manner, the paper concludes with the suggestion that due to our cultural context, creativity is observed as an act of rebellion.